(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2025)
As part of the 6th archaeological excavation campaign at the Casas del Turuñuelo site (2024), the excavation work focused on the eastern area of ​​the tumulus. Among the excavated spaces stands out a yard paved with slates and a long street that separates the main building from several rooms intended for production activities. In the so-called room P4, behind an amphora located in the southeast corner of the room, an engraved slate plate was found on which, along with several figurative and geometric motifs, an incomplete inscription of 21 signs of Southern Palaeohispanic script was placed, although there would have been room for 27. All the signs are different and match those of the Espanca abecedary, although some have distinctive variants.